Dampak Penerapan PSAK 73 Terhadap Nilai Perusahaan Transportasi dan Logistik di Indonesia Tahun 2021-2024: Aset Hak Guna dan Liabilitas Sewa - Afiandanni Naufal Rizqimarsanda; Agung Prajanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to examine the effect of right-of-use assets and lease liabilities on firm value because of the implementation of PSAK 73. The dependent variables in this study are right-of-use assets (X1), and lease liabilities (X2), while the independent variable is firm value (Y). The research focuses on transportation and logistics companies listed on the Indonesia Stock Exchange that report right-of-use assets and lease liabilities in their financial statements. The data were obtained from financial reports available on www.idx.co.id and stock prices from www.yahoo.finance.com. Using purposive sampling and outlier analysis with SPSS 25, a sample of 70 observations from 37 companies was collected. The findings indicate that right-of-use assets and lease liabilities significantly influence firm value, suggesting that these variables can serve as a reference for investors in making investment decisions